-15=b-(-65)

Simple and best practice solution for -15=b-(-65) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15=b-(-65) equation:


Simplifying
-15 = b + -1(-65)

Multiply -1 * -65
-15 = b + 65

Reorder the terms:
-15 = 65 + b

Solving
-15 = 65 + b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-1b' to each side of the equation.
-15 + -1b = 65 + b + -1b

Combine like terms: b + -1b = 0
-15 + -1b = 65 + 0
-15 + -1b = 65

Add '15' to each side of the equation.
-15 + 15 + -1b = 65 + 15

Combine like terms: -15 + 15 = 0
0 + -1b = 65 + 15
-1b = 65 + 15

Combine like terms: 65 + 15 = 80
-1b = 80

Divide each side by '-1'.
b = -80

Simplifying
b = -80

See similar equations:

| 2(-6+m)=-22 | | 2n+n+101+75=360 | | 25x^2+16y^2+100y=384 | | 39+97+n=180 | | 6n+7n+20=75 | | 65-x+2=90 | | 2m+9+6m=15 | | x-2/5x-1/6x-1/3x=1/4 | | 9x-6=21x-30 | | 4x-7=7(x-4) | | M^(2/5)*m^(1/5) | | F(x)=8x^2-10x+2 | | 2y-x-7=0 | | 4(2p+4)=40 | | 4t^2=12t-9 | | x-(.65x)=24.5 | | 10(x+3)=120 | | -4x+9=2x+57 | | x+62=57 | | 53+x=50 | | -8x+1=4x+9 | | 5(x+1)=6x+8 | | 5(x-1)=6x+8 | | 7/2x-11/2=17/2 | | 1.3=x^2+0.3 | | 9+3(x-2)=9-4(x-9) | | 1.4q-6.1q+1.4=-26.8 | | 2(x+2)+x=2(x+1)+1 | | 1.4q-6.1+1.4=-26.8 | | 9+2cosx=10 | | r=Ct+a | | m^2-7.5=92.5 |

Equations solver categories